Addressing the Use of Artificial Intelligence Tools in the Design of Visual Persuasive Discourses - Ana Erika Ruiz-Arellano; David A. Mejía-Medina; Victor H. Castillo-Topete; María Berenice Fong-Mata; Ervey L. Hernández-Torres; Paloma Rodríguez-Valenzuela; Enrique Berra-Ruiz (Designs, 2022)
Artificial intelligence (AI) systems to generate images from natural language are a game changer in graphic design. However, in visual persuasive communication, the image is not just a drawing, but is the message itself. It arises from the need for understanding how AI systems could be adopted in the design of visual communication. Thus, this article presents a model that describes the theoretical–methodological factors present in the design of persuasive visual discourses, which arises from a qualitative study with an analysis of grounded theory from the opinion of experts in the essential areas for visual communication. Thus, we propose a model to guide the design process of persuasive messages throughout seven stages. Additionally, an analysis for contributing to the orderly and informed incorporation of technologies, techniques, and methods relevant to each stage is presented.